2021
DOI: 10.4067/s0718-58392021000100102
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal efficacy and chemical composition of Balanites aegyptiaca (L.) Delile seed oils against Tribolium castaneum Herbst (Coleoptera: Tenebrionidae)

Abstract: Botanical pesticides are a new trend for pest management because they are an environmentally safe alternative for synthetic chemicals. The aim of this study was to investigate the insecticidal activity of desert date (Balanites aegyptiaca [L.] Delile) seed oils against the red flour beetle (Tribolium castaneum Herbst) and determine the oil chemical compounds by gas chromatography-mass spectrometry. Oils were extracted by chloroform, hexane, and ethanol, and they were tested on the pest by the film residue meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…(2021) reported that wild hop extracted from hexane application against granary weevil ( Sitophilus granaries ) found insect mortalities were significantly faster than acetone extract. Mokhtar et al. (2021) indicated that hexane extract from desert date seed was more toxic for red flour beetle ( Tribolium castaneum ) compared with the ethanol extract with LD 50 value of 0.327 and 3.392 mg⋅cm −2 , respectively, at 24 h after treatment by contact toxicity method.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) reported that wild hop extracted from hexane application against granary weevil ( Sitophilus granaries ) found insect mortalities were significantly faster than acetone extract. Mokhtar et al. (2021) indicated that hexane extract from desert date seed was more toxic for red flour beetle ( Tribolium castaneum ) compared with the ethanol extract with LD 50 value of 0.327 and 3.392 mg⋅cm −2 , respectively, at 24 h after treatment by contact toxicity method.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental feeds contained 10 6 , 10 7 , 10 8 and 10 9 CFU/g of live P. piscicida 2515, respectively, and 0 CFU/g served as control. After 7 days, the number of dead fish was recorded, probit analysis was used to determine median lethal dose (LD 50 ) values with SPSS version 23.0 (Mokhtar et al, 2021), and blood samples were collected from 9 fish (three replicates) by puncturing the caudal veins. The number of red blood cells was measured by haemocytometer, and the lactic dehydrogenase (LDH) activity of serum was determined by diagnostic kits (Nanjing Jiancheng Bioengineering Institute).…”
Section: Methodsmentioning
confidence: 99%
“…B. aegyptiaca oil presents interesting characteristics making it applicable in many areas including food, cosmetics and biodiesel. It also possesses medicinal properties and insecticidal activity [8][9][10]. Seed oil major fatty acids are linoleic (47.84%), oleic (22.80%), palmitic (16.68%) and stearic (11.67%) [11].…”
Section: Introductionmentioning
confidence: 99%